Impact of increased screen-time on ocular health of medical undergraduate students during COVID-19: a cross-sectional study - Mary Eldo, Basil; Elsa Mathews, Nimila; Johnson, Basil; Sara Roy, Alin (International Journal Of Community Medicine And Public Health, 2024)
Background: Digital Eye Strain (DES) or Computer Vision Syndrome (CVS) is a group of eye and vision related problems that result from prolonged use of digital devices. The usage of digital devices has gone up across the globe, since the declaration of the lockdown due to COVID-19. This study aimed to estimate the prevalence of digital eye strain (DES) due to increased screen time and to determine the factors associated with it, among undergraduate medical students during COVID-19. Methods: The study analyzed over 280 responses from undergraduate medical students having exposure to digital devices daily for a period more than 6 months during COVID 19 pandemic. A pre-validated questionnaire Computer Vision Syndrome Questionnaire (CVS-Q) which contains 16 symptoms associated with Digital Eye Strain (DES) was used to calculate the DES score. The frequency and intensity of these symptoms adds up to give a total score. A score ≥6 indicated the presence of DES. Data analysis was done using MS Excel and SPSS software. Results: Digital eye strain was found to be prevalent among 61% of the total respondents. It was seen that daily digital device usage increased to above 5 hours after commencement of pandemic (p=0·001). Headache was the most common symptom (83.92). DES has a female gender predominance (p=0.024). Conclusions: There is a high prevalence of digital eye strain among undergraduate medical students during pandemic. Awareness should be created among students about impact of DES on ocular health. Measures to reduce DES are recommended.